Targeting Id1 and Id3 by a specific peptide aptamer induces E-box promoter activity, cell cycle arrest, and apoptosis in breast cancer cells - Shenegelegn Mern, Demissew; Hoppe-Seyler, Karin; Hoppe-Seyler, Felix; Hasskarl, Jens; Burwinkel, Barbara (Breast cancer research and treatment, 2010)
Inhibitors of differentiation or DNA binding (Id) proteins have been shown to be involved in tumor growth, invasiveness, metastasis, and angiogenesis. Overexpression of Id proteins, especially Id1, correlates with unfavorable clinical prognosis. Thus, they are attractive molecular targets for anticancer therapy. Overexpression of Id proteins mediates breast cancer metastasis to lung. Targeting Id1 and Id3 expression in breast cancer cells reduces breast cancer metastasis in animal models. Different breast tumors failed to grow and/or metastasize in Id1+/−Id3−/− mice. Id1 and Id3 preferentially dimerize with the key regulatory E-proteins which inhibit the expression of different tumor suppressor genes. Nevertheless, the inhibition of tumorigenic activities of Id1 and Id3 at protein level has never been studied. Here, we isolated a novel peptide aptamer, Id1/3-PA7, specifically interacting with Id1 and Id3 from randomized combinatorial expression library using yeast and mammalian two-hybrid systems. Intracellular delivered Id1/3-PA7 co-localized to Id1 and Id3 and interfered with their functions. It repressed E47 protein sequestration by Id1 and Id3, activated the E-box promoter and increased the expression level of cyclin-dependent kinase inhibitors (CDKN1A and CDKN1B) in a dose-dependent fashion, paralleled by the cleavage of poly ADP ribose polymerase (PARP). These effects were counteracted by ectopically overexpressed Id1 and Id3. Peptide aptamer Id1/3-PA7 induced cell cycle arrest and apoptosis in breast cancer cells MCF7 and MDA-MB-231. In conclusion, Id1/3-PA7 could represent a nontoxic exogenous agent that can significantly provoke antiproliferative and apoptotic effects in breast cancer cells, which are associated with deregulated expression of Id1 and Id3.
Gesehen am 20.04.2023